Television marketing of food and beverage targeted to children, Italy. (30th September 2020) - Gianfredi, V; Rabica, F; Dallagiacoma, G; Fatigoni, C; Moretti, M; Nucci, D
Abstract: Aim: According to the World Health Organization (WHO), 40 million children aged < 5 and 131 million of children aged 5-9 are overweight or obese. Growing evidence is focusing on the association between number of hours spent watching television (TV) and children's food behaviour. Our aim was to assess the amount of TV food marketing targeted to Italian children, and to qualitatively analyse the ads. Methods: The 5 most viewed TV channels were selected and recorded for 20 days (non-consecutive, both week and week-end days) and analysed through the WHO's tool to asses food -beverage multimedia marketing targeted to children. The analysed exposure variables were: type of product, viewing time, channel's target and broadcasting company (for all types of ads), duration of each food ad, type of programme, and target of the advertised product (only for food and beverage). Power of persuasion variables were assessed only for food marketing. Lastly, for each food product showed, the food category and if it was a core vs non-core product was assessed. Differences between groups were assessed using the chi-square test and t-test. Results: During 320 hours of broadcasting TV, a total of 9, 069 ads were identified, (51.7 hours). Food products were the second most frequently advertised (19.4%). On average, 5.4 food ads were displayed during non-peak viewing time/hour (6 during peak). The time slot of 3 pm had the highest rate of food ads (23.8%). Channels targeted to the general public had a higher rate of food ads compared to channels targeted to children (p = 0.000). Private channels transmitted a higher number of food ads compared to public channels (p = 0.000). Humour was the most frequently persuasive technique used in food ads and in ads targeted to whole population (14.3%). Conclusions: Children usually watch TV programs that have a high rate of food ads, mainly promoting unhealthy products with captivating techniques. Legislators should advocate for a healthier food marketing. Key messages: Children are exposed to a high amount of TV food commercials daily. Food marketing should be strictly regulated in accordance with the WHO Nutrient Profile model.